THE POLITICAL-ECONOMIC IMPLICATIONS OF BALI NINE’S DEATH PENALTY 2015 TOWARDS THE BILATERAL RELATIONSHIP BETWEEN INDONESIAAUSTRALIA - Indi Mukti Haryandini (HI 16 UMY 009, 2016)
*9 This study tries to explain the relationship between Indonesia and Australia after the death penalty towards two citizen of Australia,Andrew Chan and Myuran Sukumaran. This study also show how the reaction of the citizen of each country ,there are a group who pro and against about the death penalty. Because of this case the cooperation between two countries became pause and relationship between Indonesia and Australia became worse. The attitude of Australia who against with this penalty is discord with the concept of sovereignty in Internationl relation study. Australian attitudes to Indonesia assessed they not respect the sovereignty and laws in Indonesia. Furthermore the theory of complex interdepende shows the cooperation between Indonesia and Australia. Indonesia and Australia are need each other to fulfill their national interest. Hence both countries could be establish good relation again. This issue could not stop the relationship between two countries.